Business Management and Globalisation (Vol. 4) : globalisation and functional management - Batra, G. S; Dangwal, R. C (editors) (New Delhi : Deep and Deep Publications Private Limited, 2002)
Business
2005\06\27
Keywords: Management; Liberalism